Morphological characteristics and nutritional value of binthe kiki, a local maize variety from Gorontalo, Indonesia - Jusna Ahmad; NOVRI YOULA KANDOWANGKO; MARGARETHA SOLANG; ERWIN NADJAMUDIN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ahmad J, Kandowangko NY, Solang M, Najamuddin E. 2021. Morphological characteristics and nutritional value of binthe kiki, a local maize variety from Gorontalo, Indonesia. Biodiversitas 22: 3523-3529. Gorontalo is among the coastal areas in Tomini bay with diverse varieties of local maize. Despite that, the population of local maize has seen a steady decline over the years. A literature study reports that local maize has adapted well to the environment in which it grows. Local maize is also hailed by the community as a source of food, animal feed, and the main ingredient of traditional medicines. The present study aims to investigate the morphological characteristics and nutritional value of binthe kiki local maize variety. Employing a quantitative descriptive method, the data of morphological characteristics were collected by referring to the maize descriptor guidelines, while the data of the nutritional value of maize kernels (regarding the proximate and mineral contents) were analyzed by referring to the Indonesian National Standard and Association of Official Agricultural Chemists (AOAC) standards. The findings show that the morphological characteristics of binthe kiki variety are as follows: (i) an average plant height of 161 cm; (ii) each stalk has three cobs with an average height of 119 cm; (iii) an average stalk circumference of 6.35 cm; (iv) an average of 12 leaves per stalk; (v) 71.12 cm of an average length of leaves; (vi) 5.21 cm of an average width of leaves; (vii) the direction of the leaf blade, on average, is slightly curved; (viii) the average leaf tip is pointed; (ix) an average cob length of 8.4 cm; (x) an average cob diameter of 2.74 cm; (xi) an average cob weight (without husk) of 0.054 kg/cob; (xii) an average of 24 kernels per row; (xiii) an average weight per 1000 kernels of 145 gram. Binthe kiki variety has high contents of protein, carbohydrate, zinc, and calcium, yet it is low in fat contents compared to other varieties.